ANALISIS KEPUASAN KERJA PEGAWAI BIRO UMUM SEKRETARIAT JENDERAL KEMENTERIAN PERDAGANGAN - Dara Puspitawati (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2021)
This research aims to find out (1) the influence of leadership style towards job satisfaction, (2) the influence of motivation towards job satisfaction, and (3) the influence of work environment towards job satisfaction. This research was held in the Ministry Of Trade, Jakarta on General Affairs Bureau Unit Of The Secretariat-General. Data retrieval was performed in February 2019. The research method used saturated sample, i.e 91 respondents. Analysis data using multiple linear regression model and processed with SPSS software version 25. The research result showed that (1) a positive and influential leadership style significanly to job satisfaction, (2) a positive and significant effect of motivation toward job satisfaction, and (3) a positive and influential work environment significanly to job satisfaction.